Social Work with Transnational Families in Japan – Transnational Social Work in the Multicultural and Integrated Community - Ayako Sasaki; Reiko Ogawa; Hanako Okawara (Asean Social Work Journal, 2022)
This paper examines social work needs for transnational families within their local areas, based on the results of a research conducted on communities with connections to Afghanistan and Sri Lankan who live in Chiba Prefecture, Japan. The research focused on speakers of three languages which are not covered by the multilingual services of the local governments despite their presence. The impact on their economic situations and daily lives due to Covid-19 arose from constraints and barriers in their surrounding environments from five primary factors, and the complex intertwining thereof: language; daily life customs/norms; residency status; employment, housing environment and community; and separation from family/relatives. We conclude that it is crucial to position transnational families within community social work along with to develop multicultural and integrated communities in order to provide transnational social work services across borders in future.